Driediger-Murphy, L.G. (2019). Roman Republican Augury. Freedom and Control - Marcattili, Francesco (ARYS. Antigüedad: Religiones y Sociedades, 2020)
DRIEDIGER-MURPHY, LINDSAY GAYLE (2019). Roman Republican Augury. Freedom and Control. Oxford: Oxford University Press. 304 pp., 66,56€ [ISBN 978-0-1988- 3443-4] [Book review]